A cross-sectional study on health related behaviors among swimming pool users and sanitary conditions of swimming pools in Hubballi city - Bathija, Geeta V.; Narasimha, Roopakala (International Journal Of Community Medicine And Public Health, 2019)
Background: With evolving and advancing civilization, man-made water recreational environments such as swimming pools, not only offer health promotions and social benefits but are also accompanied with health risks. It is necessary to properly manage and consistently monitor swimming pool to make sure about water treatment methods and health, to protect health of the users. This study aimed to assess the health related behaviours in swimming pool users and to study sanitary condition of swimming pool. Methods: A cross-sectional study done in Hubballi city among swimming pool users. A semi-structured pre-tested self-administered questionnaire applied to 200 participants of 3 swimming pools. Data collected regarding socio-demographic details, swimming pool regulations, health related events and health benefits and sanitary conditions of swimming pool. Results: Among 200 participants, 65% were males and 35% were females. 78.5% of the participants had knowledge about swimming pool regulation. 68% had unhealthy habits in swimming pool, among these 62% had at least one reported symptom. 73% of males had unhealthy habits and 57% had at least one reported symptom (p<0.05 significant). As the experience in swimming increases, unhealthy habits decreases (p<0.05 significant) and symptoms will be decreased (p<0.05 significant). Conclusions: In our study majority of the participants had unhealthy habits and knowledge about swimming pool regulations. All swimming pools were chlorinated and pH was maintained within WHO recommended guidelines.